2023
DOI: 10.3390/ijms24021248
|View full text |Cite
|
Sign up to set email alerts
|

Serosal Adhesion Ex Vivo of Hydrogels Prepared from Apple Pectin Cross-Linked with Fe3+ Ions

Abstract: The study aims to investigate the adhesion of a hydrogel made of cross-linked low-methyl esterified pectin to rat intestinal serosa ex vivo. The adhesivity of the FeP hydrogel, which was cross-linked by Fe3+ cations, exceeded that of hydrogels cross-linked by Ca2+, Zn2+, and Al3+ cations. The concentration of the cross-linking cation failed to influence the adhesion of the pectin hydrogel to the serosa. The mechanical properties and surface microrelief of the pectin hydrogel were influenced by the type and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Additionally, the introduction of Fe 3+ in such structures led to the formation of a double crosslinked network, which significantly enhanced the mechanical features of the hydrogels, and as the Fe 3+ increased from 4.76 to 13.04%, higher values of compressive strengths (495 and 820 kPa) were obtained. Popov et al [ 54 ] also reported higher hardness and compressive modulus values for pectin hydrogels resulting from an increase in the crosslinking cation concentration. For instance, an increase of 24% in hardness was obtained when the Fe 3+ concentration was increased from 21 to 42 mM [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the introduction of Fe 3+ in such structures led to the formation of a double crosslinked network, which significantly enhanced the mechanical features of the hydrogels, and as the Fe 3+ increased from 4.76 to 13.04%, higher values of compressive strengths (495 and 820 kPa) were obtained. Popov et al [ 54 ] also reported higher hardness and compressive modulus values for pectin hydrogels resulting from an increase in the crosslinking cation concentration. For instance, an increase of 24% in hardness was obtained when the Fe 3+ concentration was increased from 21 to 42 mM [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Popov et al [ 54 ] also reported higher hardness and compressive modulus values for pectin hydrogels resulting from an increase in the crosslinking cation concentration. For instance, an increase of 24% in hardness was obtained when the Fe 3+ concentration was increased from 21 to 42 mM [ 54 ]. The improvement in the mechanical properties observed for the FucoPol hydrogels is in line and consistent with the SEM observations, which revealed a stronger, compacter and more stable morphology for the HM3 membranes when compared to the HM1 or HM2 membranes ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Young's modulus was calculated using the following equation: E = (F/A)/(DH/H), where F is the force (N) measured during compression, A is the crosssectional area of the gel sample, and DH/H is the uniaxial deformation Elasticity, which indicates the capability of gels to recover their original shape after large deformations, was measured as the traveling distance of the probe that penetrated from the start of compression to a break peak. A short distance of penetration indicates a brittle gel, whereas a long distance of penetration indicates a more elastic gel [56].…”
Section: Measurement Of Mechanical Propertiesmentioning
confidence: 99%
“…Pectin has been found to attach to the glycocalyx of visceral mesothelium [18] and was proposed as a serosal bioadhesive for pleural air leaks [19][20][21] and a sealant for anastomotic healing after intestinal surgery [22]. Recently, our group showed that a hydrogel made of ionically cross-linked apple pectin adhered to rat intestinal serosa ex vivo with a strength that depended on the type of cross-linking cation [23]. However, the serosal adhesion and strength of the ionotropic pectin gel were found to decrease significantly after incubation in physiological media [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group showed that a hydrogel made of ionically cross-linked apple pectin adhered to rat intestinal serosa ex vivo with a strength that depended on the type of cross-linking cation [23]. However, the serosal adhesion and strength of the ionotropic pectin gel were found to decrease significantly after incubation in physiological media [23][24][25]. Improvement of adhesivity and strengthening of the pectin gel network appear to be necessary to obtain promising hydrogel adhesives to treat anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%